Specifics of Educational Texts Selection for Schoolchildren Doing the Humanities Subjects - T. V. Oblasova (Образование и наука)
The paper proposes the new approach to educational text selection for the humanities teaching. Its specifics is based on the wide interpretation of educational texts, as the culture texts involved in cognitive learning activity and fulfilling the multiple tasks of the related subjects and personal development. The educational text is taken as a generalized model, its content and structure determining the scheme of a speech cognitive activity, as well as the meaning formation mechanism responsible for understanding and personal development. The texts and tasks selection is oriented on schoolchildren’s understanding with the reference to the psycholinguistic, psychological and hermeneutic approaches; information extraction and interpretation level related to the author’s and student’s context. The given approach could provide the basis for developing and structuring the textbooks content for the humanities subjects.